UJI FITOKIMIA DAN AKTIVITAS ANTIBAKTERI DARI TANAMAN MERKUBUNG (Macaranga gigantea (Rchb.f. & Zoll) Mull. Arg.) DENGAN EKSTRAK TOTAL, FRAKSI n-HEKSANA, ETIL ASETAT DAN ETANOL AIR TERHADAP BAKTERI Escherichia coli dan Staphylococcus aureus - Azhar Seli Apriani; Chairul Saleh; Alimuddin - (JURNAL KIMIA MULAWARMAN, 2014)
Phytochemical tests, mortality of larvae shrimp (brine shrimp lethality test) and the antibacterial activity of theleaf merkubung (Macaranga gigantea Rchb.f. & Zoll.) With various factions has been conducted. Merkubung leafsamples were extracted with ethanol and concentrated by using rotary evaporator. The total extract was fractionatedwith n-hexane and ethyl acetate. The results of phytochemical compounds secondary metabolites merkubung leavesshowed that the total extract are contains alkaloids, phenolics and steroids. n-hexane fraction are containing alkaloids,flavonoids and steroids. Ethyl acetate faction are containing flavonoids and steroids. Ethanol-water faction is containingphenolic compounds. Shrimp larvae mortality trials showed mortality rates of larvae of Artemia salina (L) by usingSAS Probit analysis to determine the value of Lethal Concentration 50 % (LC50). The test shows that the most toxicfraction is the total extract with LC50 values of 459.8414 ppm. The test of antibacterial activity using paper disc methodand shows that the most active faction is the total extract with a MIC (Minimmum Inhibitor Concentration) of 1 % is6.5 mm diameter clear zone on Staphylococcus aureus (Gram positive) and 6.25 mm in the bacterium Escherichia coli(Gram negativ).Keywords : Macaranga gigantea Rchb.f. & Zoll., phytochemical test, Antibacteria activity test, LC50.